Goat systems of Villuercas-Ibores area in SW Spain: Problems and perspectives of traditional farming systems - Gaspar, P.; Escribano, A. J.; Mesías, F. J.; Escribano, M.; Pulido, A. F. (Small Ruminant Research, 2011)
A study of dairy goat systems was carried out in the “Villuercas-Ibores” region, a mountainous area located in the south-west of the Iberian Peninsula (Cáceres, Spain). This territory is characterized by difﬁcult orography and a fairly harsh climate, and has low indices of income and population density. Goat production in the area has contributed notably to its economic and social development historically, but there has been a marked recession in goat-based activities in recent decades, leading to changes in the type and intensity of land use. The purpose of the study is to analyze the main characteristics of the current goat farming systems in a zone in which goat milk production is possible under a Protected Designation of Origin (PDO) brand “Ibores Cheese”, and to establish a farm classiﬁcation that will allow groups of holdings with common characteristics to be identiﬁed, so that they can be compared and their performance evaluated. The data were obtained through direct interviews to goat farmers (n = 61) within the geographical area of the PDO “Ibores Cheese”. Speciﬁc information on management was collected, together with data on family characteristics, labour, livestock numbers, land use, installations, continuity, recent changes in farming, and the farmer’s opinions. A principal component analysis (PCA) was used to examine the relationships among the quantitative variables, then a two-step cluster analysis was applied using the factors obtained in the PCA and categorical variables. This resulted in a farm typology of three groups distinguished by their land use, goat breed, and PDO membership. The best management practices and productivity results were obtained by the farms furthest removed from the traditional systems. The ﬁrst group of farms is characterized by small size ﬂocks. Many of these farms do not belong to the PDO and therefore they have chosen breeds that are not allowed by the PDO regulations. Most of them are semi-intensive or intensive farms. The second group consist of extensive farms with large size ﬂocks of goats complemented with sheep farming and, occasionally, with beef cattle or Iberian pig. They have got technically suitable milking rooms, although the availability of other infrastructure is poor. Finally, the third group identiﬁed includes extensive farms whose goat ﬂock size is very similar to that of group 1, but in 70% of the cases they are mixed farms, mainly combining goat with sheep ﬂocks. Most of them are producing milk that is sold to ﬁrms producing PDO cheese. It is the group closest to the traditional farming system and the farms have small ﬂocks of low productivity per goat, raising autochthonous breeds and their crossbreeds.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Farm typology; goat systems; Management practices; multivariate analysis; PDO “Ibores Cheese”

Sheep farms in the Spanish rangelands (dehesas): Typologies according to livestock management and economic indicators - Gaspar, P.; Escribano, M.; Mesías, F. J.; Ledesma, a Rodriguez De; Pulido, F. (Small Ruminant Research, 2008)
Forty-six dehesa sheep farms of Extremadura (SW Spain) were analyzed on the basis of previously determined technical and economic indicators. A principal component analysis gave ﬁve principal components – related to intensiﬁcation, proﬁtability, and livestock mix – that characterized the farms. Using multivariate techniques based on these factors, a farm typology was established with six categories—three of sheep alone at different levels of intensiﬁcation, and three of sheep in combination with beef cattle or Iberian pig. This typology enabled homogeneous groups of farms to be considered for possible administrative actions relating to their optimal dimensions and stocking rates
Keywords: Dehesa; Farm typology; Principal component analysis; Sheep; technical and economic management

Economic and management characterization of dehesa farms: implications for their sustainability - Gaspar, P.; Mesías, F. J.; Escribano, M.; Rodríguez de Ledesma, A.; Pulido, F. (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.
Keywords: cluster analysis; Farm typology; Livestock farming systems; Principal component analysis; Rangeland management